Use of Tissue Plasminogen Activator Alteplase for Suspected Impella Thrombosis. Issue 2 (9th January 2020) - Succar, Luma; Donahue, Kevin R.; Varnado, Sara; Kim, Ju H.
Abstract : Background: Impella devices are being increasingly used to manage cardiogenic shock. The incidence of thrombosis and hemolysis in patients on Impella support increases with longer durations of use, and the management of Impella thrombosis remains ill‐defined. Methods: In this case series, we describe our institutional use of tissue plasminogen activator (tPA) alteplase in the Impella purge solution (0.04 or 0.08 mg/ml tPA in sterile water) for management of suspected Impella thrombosis in five patients, each with a different clinical course, treatment, and outcome. Given the limited evidence on the diagnosis of Impella thrombosis, suspicion was driven by the presence of decreased purge flow rates, increased purge pressures, and markers of hemolysis such as elevated lactate dehydrogenase and hematuria. Outcomes: In all cases, tPA administration resulted in resolution of low purge flow rates and high purge pressures. No major bleeding complications were directly associated with tPA. Two patients were bridged successfully to heart transplantation, two patients underwent left ventricular assist device implantation, and one patient died after withdrawal of care. Conclusion: Based on our experience, tPA administration appears to be a viable and safe salvage option to delay or prevent device exchange in the setting of suspected Impella thrombosis.